(untitled) (CIPEEX, 2025)
OBJECTIVE: To analyze the birth conditions of macrosomic babies born to mothers with gestational diabetes mellitus (GDM). METHODOLOGY: This is a descriptive and quantitative field study conducted in a pediatric outpatient clinic in the municipality of Anápolis, where the medical records of macrosomic children enrolled between 2020 and 2022 whose mothers had GDM were analyzed. RESULTS: A total of 520 medical records were analyzed. Only two records met the research criteria. The average weight of the newborns was 4350 g, both were born by cesarean section, and only one presented the main complications associated with fetal macrosomia, namely uncontrolled blood pressure and respiratory distress. CONCLUSION: Despite its low incidence, fetal macrosomia due to gestational diabetes is associated with maternal and fetal morbidity and mortality. However, due to the small sample size, further studies on fetal macrosomia are needed.